Observations on the impact of amylopectin and amylose structure on the swelling of starch granules. (June 2020) - Vamadevan, Varatharajan; Bertoft, Eric
Abstract: Four different types of amylopectin structure have been reported in our earlier work based on the internal unit chain profile obtained from limit dextrins of amylopectin and data strongly suggested that chain length and organization of internal unit chains of amylopectin influence the gelatinization and retrogradation properties of the starch. Another important functional attribute is granule swelling that mainly contributes to the viscosifying property of starches. In this study, unmodified defatted amylose-containing starch granules possessing amylopectin of four types were subjected to swelling in warm water. The swelling pattern of the granules was related to the structural type of the amylopectin component. Granules having amylopectin of Type 1 structure started to swell at lower temperature (about 55 °C) and possessed more restricted swelling than most of the other starches. Type 1 starches lost their integrity at temperatures above 85 °C, whereas starch granules with Type 2 and 3 amylopectin were still intact at 95 °C. Starches with Type 4 amylopectin were heterogeneous with respect to their swelling: Lesser yam starch possessed comparatively restricted swelling between 75 and 95 °C, whereas canna and potato starch swelled extensively and disintegrated already before 95 °C. Some waxy samples were also included in the investigation and these were generally more sensitive to swelling than their non-waxy counterparts, showing that amylose restricts the swelling and stabilizes the granular structure, albeit there was no correlation between the apparent amylose content and the swelling of tested samples. Instead, the result suggested a correlation between the structure of amylopectin and the deposition of amylose in the starch granules. Graphical abstract: Image 1 Highlights: Swelling of starch granules depends on the type of amylopectin structure. External and inter-block chain lengths influence on the swelling properties of starch granules. Amylose retards the swelling of starch granules. The structure of amylose influences on its interaction with amylopectin inter-block segments and external chain segments.